The Relationship Between Health Literacy, Self-Efficacy, and Self-Care Behaviors in Older Adults With Hypertension in the North of Iran - Azar Darvishpour; Roya Mansour-ghanaei; Fatemeh Mansouri (Health Literacy Research and Practice)
Background: Hypertension is the main risk factor for cardiovascular disease. Low level of health literacy is more common in people with hypertension. Evidence suggests that hypertension is preventable and can be controlled by modifying lifestyle and improving self-care behaviors. Objective: This study aimed to determine the relationship between health literacy, self-efficacy, and self-care behaviors in older adults with hypertension. Methods: The present study was a cross-sectional study conducted with 150 older adult patients with hypertension admitted to the Cardiac Care Unit (CCU) and post-CCU wards in East Guilan public hospitals in the north of Iran in 2020. Sampling was conducted using a convenience method based on inclusion criteria (age 60 years and older, high blood pressure and taking antihypertensive drugs for at least 6 months, ability to speak and communicate, having the suitable physical condition (not ill) to participate in research and answer questions, and having informed consent to participate in the study). The research instruments included a Health Literacy Questionnaire for Iranian Adults, a self-efficacy questionnaire in patients with hypertension, and a self-care behavior questionnaire for patients with hypertension. Descriptive statistics and multiple linear regression were used to analyze the data using SPSS software version 19. Key Results: The results showed that most patients had adequate health literacy with a mean score of 116.77 (standard deviation [SD] = 8.34), excellent self-efficacy with a mean score of 23.06 (SD = 1.99) and relatively desirable self-care behaviors with a mean score of 51.79 (SD = 4.37). Findings also indicated that health literacy can predict self-efficacy (beta = 0.262, p = .001) and self-care behaviors (beta = 0.639, p = .000). Conclusions: Based on results, health literacy is a predictor of self-efficacy variables and self-care behaviors. Therefore, planning to improve the health literacy of the older adult to promote self-efficacy and self-care behaviors and ultimately their health is recommended. [HLRP: Health Literacy Research and Practice. 2022;6(4):e262–e269.] Plain Language Summary: This study sought to determine the role of health literacy in predicting self-efficacy and self-care behaviors in older adults with hypertension admitted to CCU and post-CCU wards in East Guilan public hospitals in the north of Iran. Findings of this research demonstrate health literacy can predict self-efficacy and self-care behaviors.